Analisis Efektivitas Pengelolaan Alokasi Dana Desa Pada Anggaran Pendapatan Dan Belanja Desa Tahun 2018 Di Desa Dawan Klod, Kecamatan Dawan, Kabupaten Klungkung - Komang Ayu Diah Lestari; A.A.A.Erna Trisnadewi; L.G.P. Sri Eka Jayanti (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2020)
Abstract The aims of this study are to determine the Effectiveness of Village Fund Allocation Management in the 2018 Village Income and Expenditure Budget in Dawan Klod Village, Dawan District, Klungkung Regency, and to find out the factors that become obstacles in the Management of Village Fund Allocation in Dawan Klod Village. The sample method of this study uses a purposive sampling technique with a sample size of 30 respondents. The method uses to collect the data in this study are interviews and documentation. The data analysis uses in this study is descriptive qualitative methods with effectiveness ratios. The types of the data in this study are primary data and secondary data with research subjects consisting of the Village Government, the Village Consultative Body, the Village Community Empowerment Institute and the community of Dawan Klod Village. The result shows that the effectiveness of Village Fund Allocation Management in Dawan Klod Village in 2018 includes in the effective category, with an effectiveness level of (100%). With the support of the village program, 90% have been implemented. And at the planning stage, starting with the formation of an implementation team and the results of the development of community participation is very high and active in every activity, due to the transparency of the information conveyed by the Dawan Klod Village apparatus to the community. At the implementation stage it can be said to be effective, which is the use of the Village Fund Allocation budget can be resolved properly. In the accountability stage, the process of managing Village Fund Allocation is included in the effective category, in which the accountability report preparation is prepared by the Dawan Klod village government and there is an evaluation of activities carried out together with the Dawan Klod Village community. And in this study, there are no factors which become obstacles in the management of the Village Fund Allocation in Dawan Klod Village. Keywords: Effectiveness; Management; Village Budget and Revenue (Village Budget); Village Fund Allocation Abstrak Penelitian ini bertujuan untuk mengetahui Efektifitas Pengelolaan Alokasi Dana Desa pada Anggaran Pendapatan dan Belanja Desa Tahun 2018 di Desa Dawan Klod, Kecamatan Dawan, Kabupaten Klungkung dan untuk mengetahui faktor-faktor yang menjadi penghambat dalam Pengelolaan Alokasi Dana Desa di Desa Dawan Klod. Metode sampel dalam penelitian ini menggunakan teknik purposive sampling dengan jumlah sampel 30 responden. Metode pengumpulan data yang digunakan dalam penelitian ini adalah wawancara dan dokumentasi. Analisis data menggunakan metode deskriptif kualitatif dengan rasio efektivitas. Jenis data dalam penelitian ini adalah data primer dan data sekunder dengan subjek penelitian yang terdiri dari Pemerintah Desa, Badan Permusyawaratan Desa, Lembaga Pemberdayaan Masyarakat Desa dan masyarakat Desa Dawan Klod. Hasil penelitian menunjukan bahwa Efektifitas Pengelolaan Alokasi Dana Desa di Desa Dawan Klod Tahun 2018 termasuk dalam kategori efektif, dengan tingkat efektivitas sebesar (100%). Dengan didukung program desa yang terlaksana sebanyak 90%. Dan pada tahap perencanaan, dimulai dengan pembentukan tim pelaksana dan hasil musrembang partisipasi masyarakat sangat tinggi dan aktif disetiap kegiatan, dikarenakan transparansi informasi yang disampaikan oleh perangkat Desa Dawan Klod kepada masyarakat. Pada tahap pelaksanaan dapat dikatakan efektif, yang mana penggunaan anggaran Alokasi Dana Desa dapat terselesaikan dengan baik. Pada tahap pertanggungjawaban, proses pengelolaan Alokasi Dana Desa termasuk dalam kategori efektif, dimana penyusunan laporan pertanggungjawaban disusun oleh pemerintah Desa Dawan Klod serta adanya evaluasi kegiatan yang dilakukan bersama masyakat Desa Dawan Klod. Dan pada penelitian ini, tidak ditemukan faktor-faktor yang menjadi penghambat dalam pengelolaan Alokasi Dana Desa di Desa Dawan Klod. Kata Kunci: Efektivitas; Pengelolaan; Anggaran Pendapatan dan Belanja Desa (APB Desa); Alokasi Dana Desa